Clinical and Radiological Characteristics of Children and Adults With First-Attack Myelin Oligodendrocyte Glycoprotein Antibody Disease and Analysis of Risk Factors for Predicting the Severity at Disease Onset in Central China - Li, Yanfei; Xie, Haojie; Zhang, Jinwei; Zhou, Yongyan; Jing, Lijun; Yao, Yaobing; Duan, Ranran; Jia, Yanjie (Frontiers in Immunology, 2021)
Methods: Patients diagnosed with MOGAD at the First Affiliated Hospital of Zhengzhou University from January 2013 to August 2021 were enrolled in this retrospective study. Age at disease onset, sex, comorbidities, laboratory tests, magnetic resonance imaging (MRI) characteristics, and Expanded Disability Status Scale (EDSS) scores were collected and analyzed. The association between risk factors and initial EDSS scores at disease onset was analyzed using logistic regression models and Spearman correlation analyses. A receiver-operating characteristic (ROC) curve analysis was used to evaluate the predictive ability of the uric acid and homocysteine (Hcy) levels for the severity of neurological dysfunction at the onset of MOGAD. Results: Sixty-seven patients (female, n=34; male, n=33) with first-attack MOGAD were included in this study. The mean age at onset was 26.43±18.22 years (range: 3–79 years). Among patients <18 years of age, the most common presenting symptoms were loss of vision (36.0 %), and nausea and vomiting (24.0%), and the most common disease spectrum was acute disseminated encephalomyelitis (ADEM) (40.0%). Among patients aged ≥18 years, the most common presenting symptoms were loss of vision (35.7%), paresthesia (33.3%), and paralysis (26.2%), and the most common disease spectrum was optic neuritis (35.7%). The most common lesions were cortical gray matter/paracortical white matter lesions in both pediatric and adult patients. Uric acid (odds ratio [OR]=1.014; 95% confidence interval [CI]=1.006–1.022; P=0.000) and serum Hcy (OR=1.125; 95% CI=1.017–1.246; P=0.023) levels were significantly associated with the severity of neurological dysfunction at disease onset. Uric acid levels (r=0.2583; P=0.035) and Hcy levels (r=0.3971; P=0.0009) were positively correlated with initial EDSS scores. The areas under the ROC curve were 0.7775 (95% CI= 0.6617‒0.8933; P＜0.001) and 0.6767 (95% CI=0.5433‒0.8102, P=0.014) for uric acid and Hcy levels, respectively. Conclusion: The clinical phenotype of MOGAD varies in patients of different ages. The most common disease spectrum was ADEM in patients aged<18 years, while optic neuritis was commonly found in patients aged ≥18 years. The uric acid and Hcy levels are risk factors for the severity of neurological dysfunction at disease onset in patients with first-attack MOGAD.